2014
DOI: 10.1186/s12899-014-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of STIM1 and STIM2 during transient inward (Tin) current generation and the maturation process in the Xenopus oocyte

Abstract: BackgroundThe Xenopus oocyte is a useful cell model to study Ca2+ homeostasis and cell cycle regulation, two highly interrelated processes. Here, we used antisense oligonucleotides to investigate the role in the oocyte of stromal interaction molecule (STIM) proteins that are fundamental elements of the store-operated calcium-entry (SOCE) phenomenon, as they are both sensors for Ca2+ concentration in the intracellular reservoirs as well as activators of the membrane channels that allow Ca2+ influx.ResultsEndoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Some studies have indicated that STIM2 does not play a role in SOCE, while others have found it has a minor contribution to SOCE [ 2 , 21 , 22 , 24 , 36 , 37 , 38 , 39 , 40 ]. In contrast, STIM2 has been found to be the primary regulator of SOCE in mouse cortical neurons and Xenopus oocytes [ 41 , 42 ]. However, in rat cortical neurons, STIM1 was critical for SOCE, while STIM2 was important for regulation of resting [Ca 2+ ] ER [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have indicated that STIM2 does not play a role in SOCE, while others have found it has a minor contribution to SOCE [ 2 , 21 , 22 , 24 , 36 , 37 , 38 , 39 , 40 ]. In contrast, STIM2 has been found to be the primary regulator of SOCE in mouse cortical neurons and Xenopus oocytes [ 41 , 42 ]. However, in rat cortical neurons, STIM1 was critical for SOCE, while STIM2 was important for regulation of resting [Ca 2+ ] ER [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Silencing of STIM2 in HEK293, neutrophil-like HL-60 cells, rat pulmonary arterial smooth muscle, airway myocytes, and CD4 T + cells did not affect SOCE [ 2 , 21 , 23 , 37 , 38 , 39 ]. In contrast, knockdown of STIM2 in HeLa cells, B cells, MDA-MB-231 cells, and mouse embryonic fibroblasts (MEFs) resulted in a small reduction of SOCE, while a more significant reduction in SOCE was seen when STIM2 was silenced in murine T cells, cortical neurons, mast cells, and Xenopus oocytes [ 3 , 21 , 22 , 40 , 41 , 42 , 53 , 54 ]. Even more surprising was the finding that STIM2 inhibited SOCE when stably overexpressed in HEK293, PC12, A7r5 and Jurkat T cells [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oocyte maturation was stimulated with progesterone and validated by pERK2/ERK2 immunoblot analysis and GVBD counting. Batches of 40 defolliculated oocytes (stage VI) noninjected and injected with GIRK5K13AR14A and/or GIRK5 siRNA were incubated in 2 mL of ND96 with 10 μ m progesterone for 1, 3, 5, 7, and 10 h according to Serrano‐Flores [41]. To study the effect of barium on GVBD (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…3,103,150,151 In contrast, in Xenopus oocytes, STIM2, but not STIM1, played a predominant role in SOCE. 152 Alternatively, silencing of STIM2 expression in HEK293, neutrophil-like HL-60 cells, rat pulmonary arterial smooth muscle, airway myocytes, and CD4 T þ cells did not affect SOCE. 1,103,148,[153][154][155] In mouse neurons, where STIM2 is the dominant isoform, there was a significant reduction of SOCE following knockout of STIM2.…”
Section: Stim 2 In Soce and Ca 21 Homeostasismentioning
confidence: 97%